Analisis Penerapan Prinsip Pembelajaran dengan Menggunakan Pendekatan Understanding by Design (UbD) di Sekolah Dasar - Suci Muzfirah; Faishal Mauludhin (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study aims to determine and describe the application of learning principles using the Understanding by Design (UbD) approach. This study is a literature study with a literature review that describes the principles of learning with the Understanding by Design (UbD) approach. This study uses various documentary sources such as journals, articles, books, and documents related to this study. This literature study focuses on the Understanding by Design (UbD) approach in elementary schools. The results of the study indicate that learning with the UbD approach can be implemented well in accordance with school conditions. Student understanding is one of the focuses of success that is desired to be achieved in learning. Aspects that must be mastered by students such as the ability to explain, the ability to interpret, the ability to apply, the ability to have perspective, the ability to empathize, and the ability to have self-knowledge. This is certainly inseparable from the role of the teacher as a learning designer, where the teacher must analyze learning achievements and determine ideas, goals to be achieved and evaluations that will be given to students. The teacher facilitates all the needs of students according to their talents, interests and needs.